(untitled) (Revista de Medicina Clinica, 2025)
Introduction: Euglycemic diabetic ketoacidosis (EDKA) is an acute complication seen in insulin-deficient patients, occurring in only 2.6-3.2% of those with diabetic ketoacidosis (DKA). However, its incidence is significantly higher in pregnant diabetic patients, reaching up to 50% of DKA cases. These differences may be attributed to the specific characteristics of pregnancy, including increased counter-regulatory hormones, hyperketonemia, and limited nutritional intake. This case discusses the diagnosis, treatment, and frequency of this condition. Case Report: We present the case of a 37-year-old woman with type 1 diabetes, 33 weeks pregnant, who developed EDKA due to hyperemesis gravidarum. Metabolic acidosis was confirmed despite a serum glucose level of 175 mg/dL. Treatment included intravenous insulin, bicarbonate and appropriate intravenous glucose administration. Correct carbohydrate replenishment improved the patient’s clinical condition, leading to stabilization. Conclusions: Prevention, early diagnosis, and proper treatment, including adequate carbohydrate management, are crucial to preventing complications for both the mother and the fetus.